The effects of enoxaparin on the liver in experimental pneumoperitoneum model - Cavusoglu,Turgut (2016)
ABSTRACT PURPOSE: To investigate the potential protective effects of enoxaparin against the adverse events of carbon dioxide (CO2) pneumoperitoneum. METHODS: Thirty four rats were divided into three groups: Group 1 (sham) underwent insertion of Veress needle into the abdomen and 90 min of anesthesia with no gas insufflation. The animals in control and enoxaparin groups were subjected to 90 min of 14 mmHg CO2 pneumoperitoneum. Enoxaparin (100 u/kg) was administered subcutaneously to the rats in enoxaparin group one hour before the operation. After 90 min of pneumoperitoneum, the rats were allowed for reperfusion through 60 min. Blood and liver samples were obtained for biochemical and histopathological examination. RESULTS: Treatment with enoxaparin decreased the histopathological abnormalities when compared with the control group. The highest levels of oxidative stress parameters were found in control group. The use of enoxaparin decreased the levels of all oxidative stress parameters, but the difference between the control and enoxaparin groups was not statistically significant. CONCLUSION: Enoxaparin ameliorated the harmful effects of high pressure CO2 pneumoperitoneum on the liver.